PENGARUH PENAMBAHAN ABU SEKAM PADI (RICE HUSK ASH) DENGAN PROPORSI YANG BERBEDA TERHADAP PERTUMBUHAN SELADAI AIR (Lactuca sativa L.) - Kurniastuti, Tri; Puspitorini, Palupi; Punjungsari, Tyas Nyonita (Viabel : Jurnal Ilmiah Ilmu-Ilmu Pertanian, 2017)
Lettuce vegetables (Lactuca sativa L.) much needed by the community to meet the nutritional needs, but lettuce production is still low because of low productivity. Increasing the quality and quantity of vegetables grown on polybags is by fertilizing and arranging the composition of the planting medium. Provision of fertilizer aims to increase the supply of nutrients needed plants to boost the production and quality of crops. Fertilizer is to provide or add nutrients that plants need. However, fertilizer will tend to cause high production value and less appropriate with vegetable planting at home, therefore more optimized setting the composition of planting media. Planting media should be able to provide nutrients needed by plants. Farmers use plant residual organic materials such as rice husk as and cockpit for vegetable cultivation. The rice husk is the outermost part of the grain. The rice husk ash usually contains N 0.32%, P 0.15%, K 0.31%, Ca 0.96%, Fe 180 ppm, Mn 80.4 ppm Zn 14.10 ppm and pH 6, 8 which is expected to meet the needs of plant nutrients. The study was prepared using a complete randomized design with one factor that is the addition of planting media in the form of rice husk ash with the proportion of top soil and rice husk ash as follows: M1 (3: 1), M2 (2: 2), and M3 (1: 3). The observed variables were stem height, crown dry weight, and root dry weight. Data analysis used F Test 5% and continued with Duncan Multiple Range Test (DMRT) 5%. The results obtained at plant height of M3 (1: 3) gave the best result where there was a plant height increase of 40 cm from the first day of planting until the third day, the addition of rice husk ash did not affect the addition of root dry weight and dry weight of crown.